Overcoming stress at work - Swanson, Mandi (Chicago : Jack Wilson and Associates)
This video is offers a prescription for taming job jitters, hot tempers and other common types of anxious energy that could be draining your productivity and job satisfaction
Writer, Sara Judson Brown
Keywords: Job stress; Stress management